Laparoscopic Myomectomy vs Laparoscopically Assisted Myomectomy by Minilaparotomy: A Retrospective Study [8D]. (May 2018) - Di Francesco, Lucia; Javadian, Pouya; Nezhat, Farr; Nezhat, Camran
Abstract : INTRODUCTION: In this study we compared the short-term outcomes of laparoscopically assisted myomectomy by minilaparotomy (LAM) vs laparoscopic myomectomy (LM) for symptomatic leiomyomas. METHODS: hundred and eleven women with symptomatic leiomyomas of the uterus were included in the study. Retrospectively 51 patients with history of LM and 60 patients with history of LAM were evaluated. Patients record and history, patients characteristics, surgical course, intra and postoperative data etc. were documented and studied. Data was analyzed using SPSS. P value less than 0.05 was considered significant. RESULTS: There were no significant differences between groups regarding age, parity and BMI. Median diameter of largest myoma was significantly higher in LAM group (7.3±2.7 vs. 6.1±2.2, P value: 0.01). The median excised tissue weight in the LAM group (200 gr, range: 30-1400) vs LM group (78.5 gr, range: 20-990) was found statistically significant (P<0.005). The proportion of women with intramural fibroids and both intramural and subserosal fibroids was similar among the two groups. There was no statistically significant dependence between operation time (158.2±42.8 vs 153.1±48.4, P=0.55), median post-op hospital stay (380 min vs 398 min, P=0.37) and median estimated blood loss (600 cc vs 600 cc, P=0.64). No patients needed an admission to intensive care nor rehospitalization. Indeed, no patients in both group had post-op major complications. CONCLUSION: LAM is an acceptable alternative to LM and could have all the benefits of LM. By performing LAM, especially for larger myomas, morcellation of tissue and repair of the uterus is much easier.